Cover Picture: Enantioselective Hydroamidation of Enals by Trapping of a Transient Acyl Species (Angew. Chem. Int. Ed. 28/2018). Issue 28 (1st June 2018) - Yuan, Pengfei; Chen, Jiean; Zhao, Jing; Huang, Yong
Abstract : Asymmetric control in proton‐shuttling catalysis requires highly organized hydrogen‐bond networks, which are often disrupted by basic substrates. In their Communication on page 8503 ff., P. Yuan, J. Chen, J. Zhao, and Y. Huang demonstrate the use of azoles as transient acyl traps to secure high enantioselectivity. This strategy provides a general and enantioselective approach to diverse β‐chiral carboxylic acid derivatives from various oxygen or nitrogen nucleophiles.